STUDI PENDUGAAN ALLOMETRIK TINGKAT PERMUDAAN DI HUTAN LINDUNG GUNUNG SIRIMAU, KOTA AMBON - Frenly M. Selanno; Gun Mardiatmoko; Aryanto Boreel (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2017)
This study aims to estimate the level allometric model of regeneration in the Protection Forest of Sirimau Mountain, Ambon City. This research used purposive sampling to select plants based on criteria of sample plants grow normal and healthy. 24 plant sample was used as a sample in this study, where 14 plants sample used for the preparation of sample models and 10 plants are used to validate the model. The research data was processed through regression model to construct the model and the best model was validated using Chi-square analysis. The results showed that the model Y = 0,112D 2.14 H 0.391 with r 2 = 95.7% is the best model for estimating young woody biomass in the Protection Forest of Sirimau Mountain.